A sustainable and simple catalytic system for direct alkynylation of C(sp2)–H bonds with low nickel loadings. Issue 29 (12th March 2015) - Liu, Yue-Jin; Liu, Yan-Hua; Yan, Sheng-Yi; Shi, Bing-Feng
Abstract : A sustainable and simple catalytic system for the atom-economical alkynylation of benzamides with low nickel loadings is described. Abstract : A sustainable and simple catalytic system for the atom-economical alkynylation of benzamides with low nickel loadings is described. No organic or metallic oxidants and expensive ligands are required. A broad range of benzamides and bromoalkynes bearing various synthetically useful functional groups are compatible with this reaction. The versatility of this operationally simple protocol has been further demonstrated by the controllable mono- and di-alkynylation. Importantly, substrate/catalyst ratios of up to 200, and a turnover number of 196 were achieved, highlighting the potential of this protocol for synthetic applications.